The Jolli jeep- food trailer phenomenon in Makati (Journal of the Philippine Association for Technology in Home Economics in State Colleges and Universities, Inc., 2007)
This research examines the phenomenon of the transformed Jolli-jeeps or food trailers located in Makati City. The study aimed at characterizing the food trailer business and ascertaining emanating cultural nuances. The sample consisted of food trailers registered with the City government. The business operation was female dominated, influenced by their families who have been in a similar trade. Business was profitable, required low capital and labor cost, with controlled food cost and implying the business acumen of the food operators. They catered to a "convenient type market" whose patronage hinged on the familiarity of their food, popular prices and good taste. The study puts to the fore the shared responsibility by all family members. The legimitization of the food trailers serves as a model on how micro scale food service can be a respectable means of livelihood. Recommendations are focused on sanitation, monitoring and training. Organizing vendors into social groups in order to facilitate access by concerned agencies could also help enhance family life. The research partly lessen the anxieties on the pre-conceived notion that family life is greatly diminished by these types of business, nevertheless, the revelations should serve as springboard for other researches to deepen insight on the culture of street food life.